Trends in eclampsia in the United States, 2009–2017: a population-based study. Issue 3 (8th March 2022) - Xiao, Maggie Z.X.; Whitney, Dylan; Guo, Nan; Bentley, Jason; Shaw, Gary M.; Druzin, Maurice L.; Butwick, Alexander J.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Reducing the prevalence of eclampsia, a major cause of maternal and perinatal morbidity, is a maternal health priority. However, sparse data exist examining trends in the USA prevalence of eclampsia. Objective: The aim of this study was to assess temporal trends in the prevalence of eclampsia among live births in the United States from 2009 to 2017. Study design: This population-based cross-sectional study included live births in 41 USA states and the District of Columbia between 2009 and 2017. The prevalence of eclampsia among all women, women with chronic hypertension and hypertensive disorders of pregnancy were reported by 1000 live births. Risk ratios adjusted for maternal characteristics were used to assess temporal trends. Results: Of 27 866 714 live births between 2009 and 2017, 83 000 (0.30%) were associated with eclampsia. The adjusted risk of eclampsia decreased 10% during the 7 most recent years of the cohort, with an adjusted risk ratio of 0.90 [95% confidence interval (95% CI): 0.87–0.93] in 2017 relative to 2009. Relative to 2009, the adjusted risk of eclampsia in 2017 was substantially lower among women with chronic hypertension (adjusted risk ratio: 0.51; 95% CI: 0.46–0.57) and women with hypertensive pregnancy disorders (adjusted risk ratio: 0.43; 95% CI: 0.40–0.47). Among nonhypertensive women, there was a slight increase in the adjusted risk of eclampsia in 2017 relative to 2009 (adjusted risk ratio: 1.14; 95% CI: 1.10–1.17). Conclusion: Despite reductions in the eclampsia prevalence among women with chronic hypertension and hypertensive disorders of pregnancy, public health initiatives are needed to reduce the overall eclampsia prevalence, especially in nonhypertensive women.